Structural properties of GaN grown on AlGaN/AlN stress mitigating layers on 100-mm Si (111) by ammonia molecular beam epitaxy - Agrawal, M. (2013)
The structural properties of GaN grown on AlGaN/AlN stress mitigating layers on 100-mm diameter Si (111) substrate by ammonia molecular beam epitaxy have been reported. High resolution X-ray diffraction, micro-Raman spectroscopy, transmission electron microscopy and secondary ion mass spectroscopy have been used to study the influence of AlN thickness and AlGaN growth temperature on the quality of GaN. GaN grown on thicker AlN showed reduced dislocation density and lesser tensile strain. Three-dimensional growth regime was observed for GaN grown at lower AlGaN growth temperature while higher AlGaN growth temperature resulted in two-dimensional growth mode. The dislocation bending and looping at the AlGaN/AlN interface was found to have significant influence on the dislocation density and strain in the GaN layer. The evolution and interaction of threading dislocations play a major role in determining the quality and the strain states of GaN.